2019
DOI: 10.1016/j.inteco.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The technical decomposition of carbon emissions and the concerns about FDI and trade openness effects in the United States

Abstract: This paper decomposes the environmental Kuznets curve into the scale, technique and composition effects while incorporating the roles of energy consumption, trade openness and foreign direct investments (FDI) effects in a carbon emissions function for the United States (U.S.). We have incorporated information about unknown structural breaks into this function while investigating the cointegration between the related variables. The empirical results confirm the existence of cointegration between the variables i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(100 citation statements)
references
References 47 publications
9
90
0
1
Order By: Relevance
“…Mihci et al ( 2005 ) argue that international investment and trade help fill the technology gap among countries. Shahbaz et al ( 2019 ) argue that allowing free trading in and out of the country can improve environmental quality, but an increase in foreign investment is detrimental to a greener environment. The author suggests investment in technological innovation, capital stock, and the implementation of stringent environmental policies that will re-direct FDI towards green investment.…”
Section: Review Of Prior Studiesmentioning
confidence: 99%
“…Mihci et al ( 2005 ) argue that international investment and trade help fill the technology gap among countries. Shahbaz et al ( 2019 ) argue that allowing free trading in and out of the country can improve environmental quality, but an increase in foreign investment is detrimental to a greener environment. The author suggests investment in technological innovation, capital stock, and the implementation of stringent environmental policies that will re-direct FDI towards green investment.…”
Section: Review Of Prior Studiesmentioning
confidence: 99%
“…He found that monetary and trade policies and financial regulations contributed to the CO 2 emissions. Shahbaz et al (2019) mentioned that energy consumption, trade openness, and FDI have an influence on CO 2 emissions in the United States. Energy consumption and FDI increase CO 2 emissions, whereas trade openness declines CO 2 emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Anastacio (2017) investigated the EKC in three NAFTA countries, and other studies investigated the EKC hypothesis in the single-country case of the NAFTA region (e.g., Burnett, Bergstrom, & Wetzstein, 2013;Dogan & Turkekul, 2016;Lantz & Feng, 2006;Lipford & Yandle, 2011;Olale et al, 2018). Other than EKC, some studies also investigated the role of FDI, trade, and FMD in the pollution emissions in the single-country analysis of the NAFTA region (Dogan & Turkekul, 2016;Gale, 1995;Shahbaz et al, 2019;Waldkirch & Gopinath, 2008). But, the role of the mentioned variables in the pollution emissions of the whole North American region is missing in the literature, and spatial dependency of pollution emissions of this region also needs attention.…”
Section: Introductionmentioning
confidence: 99%
“…Dietz and Rosa (1994) reformulate the IPAT framework by considering nonproportional effects of driving forces, raising the stochastic version of this model, namely, STIRPAT (stochastic impacts by regression on population, affluence and technology). The stochastic model has been actively applied to examine all other factors affecting human impact on the environment for both developed and developing countries, such as industrial structure (Dong et al 2020, Wang et al 2016, Yu et al 2018, foreign direct investment (FDI) (Demena and Afesorgbor 2020, Mahadevan and Sun 2020, Shahbaz et al 2019, Tang and Tan 2015 and urbanization (Elliott and Clement 2014, Huo et al 2020, Khan et al 2019, Makido et al 2012, Yao et al 2018.…”
Section: Introductionmentioning
confidence: 99%